Selective laser melting of Ti alloy-Cu alloy-stainless steel multiple material part - Tey, Cher Fu (Nanyang Technological University, 2020)
The ability to combine multiple materials (MM) into a single component to expand its range of functional properties is of tremendous value to the ceaseless optimization of engineering systems. Although fusion and solid-state joining techniques have typically been used to join dissimilar metals, additive manufacturing (AM) has the potential to produce MM parts with a complex spatial distribution of materials and properties that is otherwise unachievable. In particular, powder bed fusion (PBF) processes such as selective laser melting (SLM) possesses certain desirable traits that make it attractive for MM processing. The high build resolution, small melt pool dimensions, and rapid cooling characteristics of SLM can be used to produce MM interfaces with lower dilution (i.e. less intermixing between dissimilar materials) and unique microstructural phases. Despite its potential for MM processing, little is known about its interfacial characteristics. As such, research effort was dedicated to addressing this gap. In this work, the SLM process was used to manufacture Ti alloy (TiA)/ Cu alloy (CuA)/ stainless steel (SS) MM parts which feature material transitions from 316L stainless steel to Ti-6Al-4V through an interlayer of HOVADUR® K220 Copper-alloy. The SLM of the TiA/CuA/SS MM part begun with the development of appropriate parameters to process the TiA/CuA and CuA/SS interfaces. The process parameters were devised to 1) minimize dilution and 2) maintain stable and continuous melt pools across the interfaces. Due to the composition gradient at the interface, the dimensions and stability of the melt pools varied across the interfacial build layers. To maintain consistent melt pool stability, the laser energy inputs were varied at appropriate build layers across the MM interfaces. The microstructure in both the CuA/SS and TiA/CuA interfaces were examined in detail and the former was found to contain a non-homogeneous mixture of face-centred-cubic ε-Cu and γ-Fe phases. No detrimental phases were detected at the CuA/SS interface. On the other hand, the TiA/CuA interface featured distinct layers of phase/s listed in the following order, starting from the CuA interlayer: Cu2TiAl phase, amorphous phase, and a composite layer consisting of α'-Ti reinforcements within a matrix of β-Ti+Ti2Cu phase mixture. The formation of the composite layer is attributed to the imperfect mixing and non-homogeneous Cu distribution within the melt pools. During solidification and cooling, the Cu-poor (0-5 at.% Cu) and Cu-rich (5-30 at.% Cu) regions transformed into the α'-Ti and β-Ti+Ti2Cu phase mixture respectively. The β-Ti+Ti2Cu and amorphous phase had a hardness (7.4-7.9 GPa) which exceeded that of the α'-Ti phase in the bulk TiA (4.9 GPa). Using the devised interfacial process parameters, the thickness of the L21 layer, amorphous layer, and α'-Ti+(β-Ti+Ti2Cu) composite layer can be reduced to ~1 µm, ~2 µm, and ~52 µm respectively. Such an interface also possessed a high volume fraction of α'-Ti phase (~30 vol.%) within the composite layer. Tensile fracture of the TiA/CuA/SS MM part occurred at the TiA/CuA interface. Cracks typically initiated from critically stressed pores that were located in the vicinity of a brittle phase, which was usually an amorphous region. Once initiated, the crack propagates out of the thin amorphous region and into the much thicker layer of β-Ti+Ti2Cu phase mixture. During propagation, the crack may encounter a large region of tough α'-Ti phase and, consequently, be majorly deflected towards the underlying CuA interlayer. This resulted in fracture surfaces which consists of distinct dimpled and cleavage regions belonging to the ductile CuA interlayer and the brittle TiA/CuA interface respectively. The TiA/CuA interface which possessed the highest volume fraction of interfacial α'-Ti, therefore, presented a more arduous crack propagation path with several major deflections. This led to increased fracture resistance and tensile strength in excess of 500MPa can be obtained. The reported tensile strength is among the highest for similar interfaces produced by other joining techniques reviewed in this thesis. This method of introducing an interfacial composite structure to improve MM bonding is envisioned to be applicable for the SLM of other metallic combinations.